Rethinking Schooling - Westbury, Ian; Milburn, Geoff (Education Heritage, 2007)
Taking a collection of seminal articles from the Journal of Curriculum Studies, this book offers readers a vantage point for thinking about the worlds of schools and curricula, focusing in particular on the concept of seeing schools, curricula and teaching in new ways. Each of the chapters sheds fresh light on the ways of thinking the aforementioned. Themes include: classrooms and teaching pedagogy science and history education school and curriculum development students' lives in schools. Written by an international group of distinguished scholars from Britain, North America, Sweden and Germany, the chapters draw on the perspectives offered by curriculum and pedagogical theory, history, ethnography, sociology, psychology and organisational studies and experiences in curriculum-making. Together they invite many questions about why teaching and curricula must be as they are. Rethinking Schooling provides new futures for education and alternative ways of seeing them.